Analisis Molekuler Keberadaan Patogen Malaria pada Sampel Klinis dari Labkesda Aceh Barat Berbasis Real-Time PCR - Siti Aisyah; Arif Sardi; Raudah Hayatillah; Abidah Nur; Veny Wilya (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Malaria remains a public health problem in pre-elimination areas, primarily due to the increase in cases with low parasitemia, which often go undetected by microscopic examination and potentially maintain hidden transmission. This study aims to identify the presence of malaria pathogens in clinical samples from the West Aceh Regional Health Laboratory (Labkesda) using real-time Polymerase Chain Reaction (qPCR) as a molecular confirmation approach. This study employed a quantitative descriptive design based on diagnostic surveillance. Dried Blood Spot (DBS) samples from patients exhibiting malaria symptoms were analyzed at the Banda Aceh Public Health Laboratory (Labkesmas). The results showed that four of the five samples tested positive for Plasmodium, and all were identified as Plasmodium knowlesi with Ct values ​​<40. This finding indicates the presence of malaria infections that could potentially go undetected by conventional microscopy. Thus, qPCR has the potential to be a sensitive confirmation method to support malaria case detection in surveillance activities.